Effect of antibiosis, antixenosis and natural variation of trichomes of wild and commercial tomato species on the development of Bactericera cockerelli - García-Sánchez, Adela Nazareth (2023)
Bactericera cockerelli is an economically relevant pest of solanaceous crops. The presence of leaf trichomes that certain wild species have constitutes important genetic resources for plant breeding programs in terms of resistance to pests. In this study, the influence of leaf trichomes of wild species and commercial tomato cultivars on the preference, development and fecundity of B. cockerelli was evaluated. The results showed that wild species were less preferred by the psyllid than commercial cultivars. Insects showed a lower settlement percentage in S. habrochaites compared to the other species. Regarding survival, the lowest percentage developed in S. habrochaites with 24% and S. arcanum with 40%. The lowest oviposition average was found in S. habrochaites with two eggs, which did not hatch, in addition to being the only species that showed the presence of glandular trichomes type IV (113.86 ± 48.1) and VIc (27.3 ± 2.3) per mm2, and its presence was negatively correlated with the number of perched adults. S. arcanum was another species that negatively influenced the behavior and development of the insects; however, these attributes were not due to the presence of trichomes. The defense mechanisms expressed by S. habrochaites and S. arcanum towards B. cockerelli can be used as a resource for gene introgression for the management of this pest by reducing its biological potential.